Synthesis, Carbonic Anhydrase II/IX/XII Inhibition, DFT, and Molecular Docking Studies of Hydrazide-Sulfonamide Hybrids of 4-Methylsalicyl- and Acyl-Substituted Hydrazide. (24th February 2022) - Khushal, Adil; Mumtaz, Amara; Shadoul, Wamda Ahmed; Zaidi, Syeda Huda Mehdi; Rafique, Hummera; Munir, Abida; Maalik, Aneela; Shah, Syed Jawad Ali; Baig, Ayesha; Khawaja, Wajiha; al-Rashida, Mariya; Hashmi, Muhammad Ali; et al.
Abstract : Carbonic anhydrases (CAs and EC 4.2.1.1) are the Zn 2+ containing enzymes which catalyze the reversible hydration of CO2 to carbonate and proton. If they are not functioning properly, it would lead towards many diseases including tumor. Synthesis of hydrazide-sulfonamide hybrids (19-36) was carried out by the reaction of aryl (10-11) and acyl (12-13) hydrazides with substituted sulfonyl chloride (14-18) . Final product formation was confirmed by FT-IR, NMR, and EI-MS. Density functional theory (DFT) calculations were performed on all the synthesized compounds to get the ground-state geometries and compute NMR properties. NMR computations were in excellent agreement with the experimental NMR data. All the synthesized hydrazide-sulfonamide hybrids were in vitro evaluated against CA II, CA IX, and CA XII isozymes for their carbonic anhydrase inhibition activities. Among the entire series, only compounds 22, 32, and 36 were highly selective inhibitors of h CA IX and did not inhibit h CA XII. To investigate the binding affinity of these compounds, molecular docking studies of compounds 32 and 36 were carried out against both h CA IX and h CA XII. By using BioSolveIT's SeeSAR software, further studies to provide visual clues to binding affinity indicate that the structural elements that are responsible for this were also studied. The binding of these compounds with h CA IX was highly favorable (as expected) and in agreement with the experimental data.